Systémové řešení bezpečnosti informací v organizaci - Palička, Jan (Vysoké učení technické v Brně. Fakulta podnikatelská, 2017)
Tato diplomová práce zpracovává problematiku zavedení ISMS ve společnosti Netcope Technologies, a. s., která se věnuje výrobě síťových karet pro vysokorychlostní akceleraci. Práce je rozdělena na dvě logické části. V první části je uveden teoretický základ práce, včetně vybraných metod pro zavedení bezpečnosti informací. Ve druhé části potom analýza společnosti a navrhovaná opatření.

This diploma thesis deals with ISMS implementation in Netcope Technologies, a. s., which is involved in the production of network cards for high speed acceleration. This thesis is divided into two logical parts. In the first part the theoretical basis information is presented, including selected methods for implementing information security. In the second part, the analysis of the company and the proposed measures are presented.
Systematic Solution for Information Security in Organisation
Keywords: ISMS; informační bezpečnost; analýza rizik; hrozby; opatření; ČSN ISO/IEC 27000; ČSN ISO/IEC 27001; ČSN ISO/IEC 27002; ČSN ISO/IEC 27005; ISMS; Information Security; risk analysis; threads; measures; ČSN ISO/IEC 27000; ČSN ISO/IEC 27001; ČSN ISO/IEC 27002; ČSN ISO/IEC 27005.